2017
DOI: 10.17148/ijarcce.2017.6722
|View full text |Cite
|
Sign up to set email alerts
|

A Proposal on Initial Remote User Enrollment for IVR-based Voice Authentication Systems

Abstract: In the last decade, Interactive Voice Response (IVR) systems gained popularity among customer care, phone banking and many other commercial services. It helps to reduce conversation and dialing overheads, guides customers and automates call forwardings. On the other hand, many sensitive phone and online services, including banking operations and e-government applications, require strict and accurate user/customer authentication schemes. Although not being preferred so far, with regards to the recent developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Since the user has a pc or a mobile device, or any device that can be connected to the internet, he can be capable of voting in a way which lawmakers and directors or managers will be capable of accessing the people's lowest conclusions. By this, real majority rule government will be accomplished automatically (Çabuk, Şenocak, Demir, & Çavdar, 2017). It is integral to be controlled without problems precisely in little towns, and certainly in more significant cities discovered in degenerate nations.…”
Section: Related Workmentioning
confidence: 99%
“…Since the user has a pc or a mobile device, or any device that can be connected to the internet, he can be capable of voting in a way which lawmakers and directors or managers will be capable of accessing the people's lowest conclusions. By this, real majority rule government will be accomplished automatically (Çabuk, Şenocak, Demir, & Çavdar, 2017). It is integral to be controlled without problems precisely in little towns, and certainly in more significant cities discovered in degenerate nations.…”
Section: Related Workmentioning
confidence: 99%
“…Providing this anonymity is also a major challenge in the current state-ofthe-art works. Hao et al in their work, proposed a solution based on the Diffie-Hellman process, which also implies the use of public/private key pairs and random numbers, so that a "two-round" referendum can supposedly be held with some ballot privacy [12] IV. CONCLUSION…”
Section: International Journal Of Engineering Research and Technology (mentioning
confidence: 99%
“…This also explains why Estonia still holds both traditional and online elections together. Several studies showed that the trust in such electronic voting systems are considerably low (or at least not high as the traditional systems) [23], and some institutions and researchers started to propose ways to improve that trust already [24][25]. The trust in e-voting, if can be increased successfully, would even increase the overall trust to the general political system, especially in the developing countries [26].…”
Section: B Social Aspectsmentioning
confidence: 99%